2020
DOI: 10.5334/tismir.37
|View full text |Cite
|
Sign up to set email alerts
|

User Models for Culture-Aware Music Recommendation: Fusing Acoustic and Cultural Cues

Abstract: Integrating information about the listener's cultural background when building music recommender systems has recently been identified as a means to improve recommendation quality. In this article, we, therefore, propose a novel approach to jointly model users by their musical preferences and cultural backgrounds. We describe the musical preferences of users by the acoustic features of the songs the users have listened to and characterize the cultural background of users by culture-related socioeconomic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Additionally, since previous research has shown that the listener's cultural background impacts the quality of music recommendations [47], we plan to compare the cultural and socioeconomic aspects of beyond-mainstream and mainstream music listeners. We plan to employ these aspects by means of Hofstede's cultural dimensions [82] and the World Happiness Report [83].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, since previous research has shown that the listener's cultural background impacts the quality of music recommendations [47], we plan to compare the cultural and socioeconomic aspects of beyond-mainstream and mainstream music listeners. We plan to employ these aspects by means of Hofstede's cultural dimensions [82] and the World Happiness Report [83].…”
Section: Discussionmentioning
confidence: 99%
“…We base our work on a dataset gathered from the Last.fm music platform, which we considerably enrich with the music tracks' acoustic features (see Sect. 3.1) [48]. Additionally, we combine this data with mainstreaminess information of Last.fm users (see Sect.…”
Section: Enriched Dataset Of Music Listening Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…We will also explore more refined sampling strategy [64,45] in order to reduce the computational time while keeping the performance high. Besides, our work can be extended to handle other modalities in order to fully exploit the available content such as artists biographies [65] or musical tags [16,66,28], but also contextual data such as culture [67] or location [5]. Finally, alternative architectures could be exploited, such as convolutional networks that directly extract content features from the raw audio data [36] in an end-to-end fashion.…”
Section: Discussionmentioning
confidence: 99%